2013
DOI: 10.1159/000356128
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chromosome Markers from the Lake Victoria Cichlid Paralabidochromis chilotes and Their Application to Comparative Mapping

Abstract: Cichlid fishes in the African Great Lakes are known as a spectacular example of adaptive radiation in vertebrates. Four linkage maps have been constructed to identify the genes responsible for adaptation and speciation, and the genetic linkages of those genes are assumed to play an important role during adaptive evolution. However, it is difficult to analyze such linkages because the linkage groups of one species do not match well with those of the other species. Chromosome markers are a powerful tool for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…As shown in Table 2, the cichlid LGs 15 and 19 correspond to LG3 (and the small LGs 24 and 25) of A. burtoni, suggesting that LG3 of A. burtoni has emerged by chromosomal fusion. The result of our genetic linkage map analysis is consistent with a study by Kuroiwa et al (2014), who performed a comparative mapping between H. chilotes and A. burtoni by BAC fluorescence in situ hybridization (FISH) using 19 BAC clones. They suggested that chromosome 2 of A. burtoni emerged by the fusion of two chromosomes, one of which possesses a marker for cichlid LG19.…”
Section: Chromosomal Fusion In a Burtonisupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Table 2, the cichlid LGs 15 and 19 correspond to LG3 (and the small LGs 24 and 25) of A. burtoni, suggesting that LG3 of A. burtoni has emerged by chromosomal fusion. The result of our genetic linkage map analysis is consistent with a study by Kuroiwa et al (2014), who performed a comparative mapping between H. chilotes and A. burtoni by BAC fluorescence in situ hybridization (FISH) using 19 BAC clones. They suggested that chromosome 2 of A. burtoni emerged by the fusion of two chromosomes, one of which possesses a marker for cichlid LG19.…”
Section: Chromosomal Fusion In a Burtonisupporting
confidence: 90%
“…As a result, we found that the cichlid individuals used in the present study do not possess B chromosomes. It is therefore, the number of LGs (25) is different from the chromosome number (2n = 44) of LV cichlids (Yoshida et al, 2011;Kuroiwa et al, 2014). We expected that some of the linkage groups will be joined to…”
Section: Genetic Linkage Map Of LV Cichlidsmentioning
confidence: 99%
“…Cichlids are an established model for evolutionary studies due to their fast adaptive radiation in East Africa (Kocher 2004) and have also become a model for the study of B chromosomes. Notably, Bs have been identified in 7 South American (Feldberg and Bertollo 1984;Martins-Santos et al 1995;Feldberg et al 2004) and 14 African (Poletto et al 2010a, b;Yoshida et al 2011;Kuroiwa et al 2014) species of cichlids. Astatotilapia latifasciata is an African cichlid fish found in Lake Nawampasa (satellite lake of Lake Kyoga, part of Lake Victoria system) and is a widely distributed species in the aquarium hobbyist trade (Skelton 2001).…”
Section: Introductionmentioning
confidence: 99%
“…B chromosomes are femalespecific in Lithochromis rubripinnis (cichlids of Lake Victoria, East Africa), and crosses demonstrated that the presence of B leads to a female-biased sex ratio (Yoshida et al 2011). However, B chromosomes have been associated with both males and females in 12 other cichlid species in Lake Victoria, including A. latifasciata (Poletto et al 2010a(Poletto et al , 2010bYoshida et al 2011;Kuroiwa et al 2014). B chromosomes were also inferred only in females among seven species in Lake Malawi (East Africa) cichlids (M. lombardoi, M. zebra BBoadzul,^M.…”
Section: Sex-related Variationsmentioning
confidence: 99%
“…Among the African cichlids, B chromosomes were first described in Astatotilapia latifasciata from Lake Nawampasa, a satellite lake of Lake Kyoga (part of the Lake Victoria system) and in Metriaclima lombardoi from Lake Malawi in East Africa (Poletto et al 2010a(Poletto et al , 2010b. Subsequently, B chromosomes were identified in 12 species of African cichlids of Lake Victoria (Yoshida et al 2011;Kuroiwa et al 2014) and more than six species of Lake Malawi (Clark et al 2017). The cichlid fish A. latifasciata harbors zero, one, or two B chromosomes and was previously studied through classical and molecular cytogenetics studies.…”
Section: Introductionmentioning
confidence: 99%